The Effectiveness of Ginger Herbal Drink in Reducing the Frecuency of Nausea and Vomiting in the First Trimester Pregnant Women - Ana Yuliana; Tiara Fatma Kumala; Dian Karisma Putri; Aureo Frutalegio da Costa Freitas; Fabiola Francisca Martins Soares (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
The incidence of nausea and vomiting is often experienced by pregnant women in the first trimester pregnant women. This is due to hormonal changes in early pregnancy. Efforts to reduce frequency of nausea and vomiting can be with food or drinks containing ginger. Ginger is kind of herbs which has been known to prevent nausea and vomiting. The purpose of this study was to analys the effectiveness of ginger herbal drink in reducing the frequency of nausea and vomiting in the first trimester pregnant women. The design of this research is Pre-Experimental Design with one group prestest-posttest. The population in this study were first trimester pregnant women. The sample in this study amounted to 32 taken using total sampling. Collecting data used using an observation sheet filled in by the respondent for 2 weeks in the form of pre-post. Analysis of the data used wilcoxon test. The result of the study was the value of the statistical test output is known as the Asymp value. Sig. (2-tailed) is worth 0.000. Asymp Value. Sig. (2-tailed) < 0.005, it can be concluded that "Ha" is accepted, which means that there is a difference between the frequency of nausea and vomiting in pregnant women before being given ginger drink and after being given ginger drink. So it can be concluded "there is an effect between drinking ginger on the frequency of nausea and vomiting in pregnant women". Expected for the pregnant women can take advantage of ginger herbal drink as an alternative treatment to reduce the frequency of nausea and vomiting in the first trimester.